Educational Values For Children Based On Qs. Luqman: 13-14 In Digital Era - Murharyana Murharyana; Ibnu Imam Al Ayyubi; Sabrina Yasmin; Dede Ahmad Riyadi; Cep Hasbi Maulana (Al Muhafidz: Jurnal Ilmu Al-Qur'an dan Tafsir, 2024)
This research aims to outline and explore the concept of educational values for children in digital era which is based on QS. Luqman: 13-14. The method used in this research is descriptive qualitative approach. Data collection techniques used observation and interviews. Data analysis techniques include data collection, data reduction, data presentation, and concluding. According to the results of this research, it is concluded that through the values contained in QS. Luqman: 13-14, bad deeds due to dehumanization and degradation can be addressed and prevented from an early age. The educational value of QS. Luqman verse 13 is to emphasize parents to keep their children away from acts of shirk and verse 14 is to emphasize for children to be good to parents and uphold gratitude. In this research, it can be concluded that the development of the digital era has greatly influenced human life to experience many significant changes. One of the changes occurs in children’s education which is assimilated with westernization and technology in it so that potential decadence occurs.